2012
DOI: 10.1126/scitranslmed.3004276
|View full text |Cite
|
Sign up to set email alerts
|

An Orally Active TRPV4 Channel Blocker Prevents and Resolves Pulmonary Edema Induced by Heart Failure

Abstract: Pulmonary edema resulting from high pulmonary venous pressure (PVP) is a major cause of morbidity and mortality in heart failure (HF) patients, but current treatment options demonstrate substantial limitations. Recent evidence from rodent lungs suggests that PVP-induced edema is driven by activation of pulmonary capillary endothelial transient receptor potential vanilloid 4 (TRPV4) channels. To examine the therapeutic potential of this mechanism, we evaluated TRPV4 expression in human congestive HF lungs and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
334
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(365 citation statements)
references
References 43 publications
28
334
2
1
Order By: Relevance
“…The recent discovery of its localization to cilia suggested its potential role in the pathophysiology of glaucoma in the TM of eyes (4,6,7). TRPV4 has been well recognized to be a mechanosensor in kidney epithelial cells, as well as in a number of other fluidregulating cell types (32,37,38,40). Here we show that OCRL interacts with TRPV4.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The recent discovery of its localization to cilia suggested its potential role in the pathophysiology of glaucoma in the TM of eyes (4,6,7). TRPV4 has been well recognized to be a mechanosensor in kidney epithelial cells, as well as in a number of other fluidregulating cell types (32,37,38,40). Here we show that OCRL interacts with TRPV4.…”
Section: Discussionmentioning
confidence: 54%
“…TRPV4 is a mechanosensitive calcium-permeable cation channel that localizes to cilia, where it functions in osmotic regulation (32,(37)(38)(39). TRPV4 dysregulation has been implicated in diseases with fluid overload, such as hydrocephalus and heart failure (32,40). Therefore, we investigated if OCRL and TRPV4 may play a role in TM cilia.…”
Section: Resultsmentioning
confidence: 99%
“…TRPV4 has been implicated recently in the differentiation of chondrocytes, osteoclasts, and cardiac myofibroblasts via Ca 2+ influx (29)(30)(31). It has been reported that TRPV4 initiates the acute calcium-dependent vascular permeability in pulmonary edema that develops upon ventilator-induced lung injury or by elevated pulmonary venous pressure associated with heart failure in mice (32,33). However, TRPV4 has not been previously shown to be involved in lung myofibroblast differentiation or fibrosis, and the molecular mechanism of its involvement in this process has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The team already has used the lung-on-a-chip model in proofof-concept studies to test potential pulmonary edema therapeutic candidates including GlaxoSmithKline plc's GSK2193874, an inhibitor of transient receptor potential vanilloid 4 (TRPV4; VRL2), 3 and wants to expand the use of the chip to model multiple lung diseases.…”
Section: By Lauren Martz Staff Writermentioning
confidence: 99%
“…in a paper published in Science Translational Medicine, 3 Kevin thorneloe and colleagues used small molecule screening and chemical optimization to develop GsK2193874. thorneloe is a senior scientific investigator at GsK.…”
Section: By Lauren Martz Staff Writermentioning
confidence: 99%